Immune and antioxidant responses of pearl oyster Pinctada maxima exposed to acute salinity stress. (6th February 2022) - Wei, Haijun; Chen, Mingqiang; Deng, Zhenghua; Zhao, Wang; Li, Youning; Fang, Wei; Ma, Zhenhua; Wang, Yu; Yu, Gang
Abstract: Salinity change is a frequently occurring abiotic stress that dramatically affects the physiological and biochemical factors of marine bivalve molluscs. In this study, a total of 140 individuals of Pinctada maxima were collected from Weizhou Island (Beihai, China) for 48‐h acute salinity stress. Immune enzymes (phenoloxidase [POX], lysozyme [LZM] and alkaline phosphatase [ALP]), antioxidant enzymes and substances (superoxide dismutase [SOD] and reduced glutathione [GSH]) were measured at different times after acute low‐salinity (salinity 20) and high‐salinity (salinity 40) stress with a salinity of 30 as the control group to assess the effects of acute salinity stress on immune and antioxidant responses of P . maxima . The results showed that the total protein (TP), GSH, SOD, POX, LZM and ALP of silver‐lipped pearl oyster P . maxima were significantly influenced by the different salinity gradients and duration of salinity stress ( p < 0.05). The TP, SOD, LZM and GSH of P . maxima recovered to the same level of the control group at 48 h after acute high‐salinity stress (salinity 40, p > 0.05), while only TP and LZM in the low‐salinity group (salinity 20) recovered to the same level of the control group at 48 h ( p > 0.05), indicating that P . maxima has a stronger tolerance to high salinity (40) than low salinity (20). The study provides references for exploring the antioxidant and immune response mechanism to salinity stress in P . maxima and its cultivation.